China-Africa media relations: What we know so far. Issue 2 (June 2018) - Wasserman, Herman
The increased presence of Chinese media in Africa has been a topic of much debate in recent years, and has given rise to a burgeoning research area. Seen as a platform upon which China can exert its 'soft power' in Africa as part of its outward-looking international relations policy, Chinese media has been considered instrumental in portraying a more positive picture of China among African audiences, partly in an attempt to support the expansion of Chinese economic activities on the continent. Critics have however questioned the influence that Chinese media practices may have on journalistic value systems and press freedom on the continent. These criticisms assume that Chinese media may have a big impact on African media, although the empirical basis for such claims have often been lacking.